+0  
 
0
1031
1
avatar+598 

Let $f(x)$ be the polynomial \[f(x)=3x^4+5x^2-9x-2.\] If $g(x)$ is equal to the polynomial $f(x-1)$, what is the sum of the coefficients of $g$?

 Sep 10, 2017
 #1
avatar+98090 
+2

 

f(x -1)  = 3(x-1)^4 + 5(x-1)^2 - 9(x-1) - 2  =

 

3 (x^4 - 4x^3 + 6x^2 - 4x + 1) + 5(x^2 - 2x + 1) - 9 (x - 1) - 2 =

 

3x^4 - 12x^3 + 23x^2 - 31x + 15  =  g(x)

 

The sum of the coefficients of g(x)  =  3 - 12 + 23 - 31 + 15  =  -2

 

 

cool cool cool

 Sep 10, 2017

26 Online Users

avatar
avatar
avatar
avatar